The genetic and clinical outcome of isolated fetal muscular ventricular septal defect (VSD). (2nd September 2019) - Svirsky, Ran; Brabbing-Goldstein, Dana; Rozovski, Uri; Kapusta, Livia; Reches, Adi; Yaron, Yuval
Abstract: Introduction: Our objective was to evaluate the incidence of chromosomal aberration (both microscopic and submicroscopic) and the clinical outcome of fetuses with isolated muscular ventricular septal defect (VSD). Material and methods: The study included 40 pregnant women whose fetuses were diagnosed with isolated muscular ventricular septal defect (mVSD). Of these, 30 patients underwent amniocentesis and 10 declined. All samples were tested by chromosomal microarray analysis (CMA). Of the 40 women in the study, 32 gave birth and the clinical outcome of the children was retrieved from the patients' medical records. Results: Of the 30 patients who underwent amniocentesis, one was detected with mosaic Klinefelter syndrome and one was detected with a pathogenic copy number variant unrelated to the VSD. Clinical follow-up was performed on 26 children after birth. The first postnatal echocardiography did not detect a VSD in 13 (50%) of the followed-up children. Spontaneous closure occurred in another eight (30.8%) children during the postnatal follow-up period. In only five children (19.2%) VSD was still detected by echocardiography after the first year of life. Discussion: Isolated muscular VSD diagnosed prenatally does not appear to be a significant risk factor for chromosomal abnormalities and has a favorable clinical outcome.